Risk Factors for Central Venous Access Device-Related Thrombosis in Hospitalized Children: A Systematic Review and Meta-Analysis - Tian, Lingyun; Li, Wan; Su, Yanan; Gao, Huimin; Yang, Qiuhong; Lin, Pan; Wang, Liqian; Zeng, Jiaqi; Li, Yinglan (Thrombosis and Haemostasis, 2020)
Objective To identify the potential associations of patient-, treatment-, and central venous access device (CVAD)-related factors with the CVAD-related thrombosis (CRT) risk in hospitalized children.Methods A systematic search of PubMed, EMBASE, Web of Science, the Cochrane Library, China National Knowledge Infrastructure, Wanfang, and VIP database was conducted. RevMan 5.3 and Stata 12.0 statistical software were employed for data analysis.Results In terms of patient-related factors, the patient history of thrombosis (odds ratio [OR] = 3.88, 95% confidence interval [CI]: 2.57–5.85), gastrointestinal/liver disease (OR = 1.85, 95% CI: 0.99–3.46), hematologic disease (OR = 1.45, 95% CI: 1.06–1.99), and cancer (OR = 1.58, 95% CI: 1.01–2.48) were correlated with an increased risk of CRT. In terms of treatment-related factors, parenteral nutrition (PN)/total PN (OR = 1.70, 95% CI: 1.21–2.39), hemodialysis (OR = 2.17, 95% CI: 1.34–3.51), extracorporeal membrane oxygenation (OR = 1.51, 95% CI: 1.31–1.71), and cardiac catheterization (OR = 3.92, 95% CI: 1.06–14.44) were associated with an increased CRT risk, while antibiotics (OR = 0.46, 95% CI: 0.32–0.68) was associated with a reduced CRT risk. In terms of the CVAD-related factors, CRT risk was more significantly increased by peripherally inserted central catheter than tunneled lines (OR = 1.81, 95% CI: 1.15–2.85) or totally implantable venous access port (OR = 2.81, 95% CI: 1.41–5.60). And subclavian vein catheterization significantly contributed to a lower CRT risk than femoral vein catheterization (OR = 0.36, 95% CI: 0.14–0.88). Besides, multiple catheter lines (OR = 4.06, 95% CI: 3.01–5.47), multiple catheter lumens (OR = 3.71, 95% CI: 1.99–6.92), central line-associated bloodstream infection (OR = 2.66, 95% CI: 1.15–6.16), and catheter malfunction (OR = 1.65, 95% CI: 1.07–2.54) were associated with an increased CRT risk.Conclusion The exact identification of the effect of risk factors can boost the development of risk assessment tools with stratifying risks.
Keywords: risk factors; thrombosis; deep vein thrombosis; prevention